The New Media Operating System (NMOS): A Synthesis Model of Deconglomeration, Decentralization, and Demassification in the New Media Communication Domain - Prabu Revolusi; Wishnutama Kusubandio; Radians Krisna Febriandy (Greenation International Journal of Law and Social Sciences, 2026)
Title: The New Media Operating System (NMOS): A Synthesis Model of Deconglomeration, Decentralization, and Demassification in the New Media Communication Domain. Object: The five operational mechanisms through which organic new media entities function within the ecosystem produced by deconglomeration, decentralization, and demassification, studied within the Indonesian media landscape as primary empirical context. Method: This study employs a systematic literature review of 38 sources selected from 412 initial articles spanning 2020 to 2025, grounded in the New Media Communication Domain framework, Media morphosis, and Teknologimorfosis, supported by secondary empirical data on media consumption, entity growth, advertising expenditure, and audience behavior in Indonesia. Results: The NMOS model identifies five operational mechanisms: algorithmic gatekeeping, attention economy architecture, prosumer and participatory production, datafication, and platform governance. A critical conceptual correction establishes that platform technology corporations such as YouTube, Meta, and TikTok are digital distribution infrastructure analogous to the printing press, not media entities. Secondary data from Indonesia document a 165-fold growth in registered online media entities between 2010 and 2023 and a television advertising share decline from 68 to 33 percent between 2015 and 2024, with organic YouTube creators consistently outperforming legacy television channels. Conclusion: The NMOS model constitutes a synthesis of the three structural transformation processes and provides scholars with an integrated analytical framework and policymakers with a basis for infrastructure-targeted media regulation in the platform era.